Drug interactions in dermatology: What the dermatologist should know - Arijit Coondoo; Chandan Chattopadhyay (Wolters Kluwer Medknow Publications, 2013)
A drug interaction is a process by which a drug or any other substance interacts with another drug and affects its activity by increasing or decreasing its effect, causing a side effect or producing a new effect unrelated to the effect of either. Interactions may be of various types-drug-drug interactions, drug-food interactions, drug-medical condition interactions, or drug-herb interactions. Interactions may occur by single or multiple mechanisms. They may occur in vivo or in vitro (pharmaceutical reactions). In vivo interactions may be further subdivided into pharmacodynamic or pharmacokinetic reactions. Topical drug interactions which may be agonistic or antagonistic may occur between two drugs applied topically or between a topical and a systemic drug. Topical drug-food interaction (for example, grape fruit juice and cyclosporine) and drug-disease interactions (for example, topical corticosteroid and aloe vera) may also occur. It is important for the dermatologist to be aware of such interactions to avoid complications of therapy in day-to-day practice.